Development and Validation of the Folin-Ciocalteu Semi-Micro Method for Total Phenolic Compounds Determination in Rangdaeng (Ventilago denticulata Willd.) Extract - Srimoon, Rawinipa; Niyomwan, Sirikamol (Burapha Science Journal, 2026)
The purposes of this research were to develop and validate the Folin-Ciocalteu semi-micro method for total phenolic compounds determination in Rangdaeng (Ventilago denticulata Willd.) extract. The results showed that the optimum condition was as follows: 100 mL of sample, 250 mL of 20%v/v Folin-Ciocalteu phenol reagent, 100 mL of 3.75%w/v Na2CO3 and 40 minutes of the equilibrium time using gallic acid as the standard. The absorbance at 765 nm was no significant difference (P>0.05) compared with the conventional Folin-Ciocalteu meso-method (20 folds in volume of the sample and reagents). Method validation revealed good linearity (R2>0.999) and specificity (calibration curve and specificity curve were paralleled with 0-5.91% of slope difference). LOD and LOQ was 3.70 and 11.22 mg/mL, respectively. Accuracy and precision of the method were acceptable. Percentage of recovery and %RSD were in the range of 82.11-105.31 and 4.77-6.42, respectively. Repeatability (intra-day), reproducibility (inter-day) and intermediate-precision method as %RSD were 0.77-2.42, 2.41-3.63 and 1.39-3.26, respectively. Method also showed the robustness under temperature in the range of 20-50 oC (%RSD=0.21-6.03). The developed Folin-Ciocalteu semi-micro method was applied to the determination of total phenolic compounds (TPC) in Rangdaeng (V. denticulata) extract, compared with the Folin-Ciocalteu meso-method. The results showed that the TPC were 73.87±0.75 and 74.61±0.82 mg GAE/g dw, respectively, which were not different significantly (P>0.05). In conclusion, the Folin-Ciocalteu semi-micro method is appropriated to the routine assay. Due to the decreasing in the reaction time, it is faster. This method reduces solution volume, chemical usage and wasted discharge so it is more environmental-friendly and safer.